Weaknesses of E-Commerce Regulations in Protecting Couriers from Consumer Default Risk in COD Transactions - Diwan Jagad Raya Mohamad; Dolot Alhasni Bakung; Fitran Amrain (Dalihan Na Tolu: Jurnal Hukum, Politik dan Komunikasi Indonesia, 2026)
The rapid growth of e-commerce and cash-on-delivery (COD) transactions in Indonesia has exposed a critical regulatory gap: delivery couriers remain legally unprotected against consumer default, despite bearing substantial operational and financial risks. This study examines the weaknesses of Indonesian e-commerce regulations in protecting couriers from consumer default in COD transactions. Employing a normative legal research method with statutory and conceptual approaches, supported by empirical data from semi-structured interviews with couriers and documentation of dispute cases, this study reveals two fundamental regulatory failures. First, the current legal framework, particularly Law No. 8 of 1999 on Consumer Protection, remains trapped in an outdated bipartite paradigm that recognizes only consumers and business actors, rendering couriers legally invisible and devoid of clear legal standing. Second, existing protections are exclusively repressive, responding to harm only after disputes or violence occur, while no preventive mechanisms such as mandatory compensation schemes, buyer verification systems, or accessible dispute resolution exist to deter consumer default or mitigate couriers' economic losses. Consequently, couriers bear the entire risk of default despite having no control over product quality or consumer conduct. This study concludes that legislative reform is urgently needed to recognize couriers as distinct legal subjects and to establish preventive-protective regulations ensuring justice for essential workers in Indonesia's digital economy.